(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Even though many companies have a large number of KM implementation projects, many of them are designed as stand-alone initiatives with no link to the organization’s strategy. We are seeing how KM programs are failing to provide the promised results. As a result, investigating the elements that influence KMM is crucial. The present study is based on applied research and is a survey. The goal of this report was to look into and assess the elements that influence KMM, and Guilan customs were chosen as a case study because of the relevance of the KM dilemma in customs. The study’s statistical population includes all Guilan provincial customs managers and experts. A basic random approach was utilized for sampling, and data was collected using a Likert scale questionnaire. The probability sampling was computed utilizing Krejcie and Morgan method and was found to be 84. Professors and professionals assisted in the testing including the questionnaire’s validity. Cronbach’s alpha coefficient was also used to determine dependability. Leadership, human resources, KM infrastructure, business culture, and the KM process all influence KMM, according to the research.